Learn OpenOffice.org spreadsheet macro programming : OOoBasic and Calc automation : a fast and friendly tutorial to writing macros and spreadsheet applications /: OOoBasic and Calc automation : a fast and friendly tutorial to writing macros and spreadsheet applications. (2006) - Unknown
No abstract available